2018
DOI: 10.1016/j.nicl.2018.09.025
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities are linked to future cognitive decline in de novo Parkinson's disease patients

Abstract: White Matter Hyperintensities (WMHs) are associated with cognitive decline in aging and Alzheimer's disease. However, the pathogenesis of cognitive decline in Parkinson's disease (PD) is not as clearly related to vascular causes, and therefore the role of WMHs as a marker of small-vessel disease (SVD) in PD is less clear. Currently, SVD in PD is assessed and treated independently of the disease. However, if WMH as the major MRI sign of SVD has a higher impact on cognitive decline in PD patients than in healthy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
53
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 67 publications
10
53
2
Order By: Relevance
“…Although surprising, this is in agreement with previous studies showing a positive impact of hyperlipidimia on lowering WMH burden in three independent large samples, suggesting a relatively protective role of hyperlipidimia on small-vessel disease 42,43 . Unlike previous studies, we did not find an association between hypertension and WMH burden 16,42 (Table 2). This might be due to the relatively smaller sample size or that the blood presure levels were well-controlled in both controls and PD patients in our sample (Table 1).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although surprising, this is in agreement with previous studies showing a positive impact of hyperlipidimia on lowering WMH burden in three independent large samples, suggesting a relatively protective role of hyperlipidimia on small-vessel disease 42,43 . Unlike previous studies, we did not find an association between hypertension and WMH burden 16,42 (Table 2). This might be due to the relatively smaller sample size or that the blood presure levels were well-controlled in both controls and PD patients in our sample (Table 1).…”
Section: Discussioncontrasting
confidence: 99%
“…WMH volume increased with age in both controls and PD patients (Figure 2.e). Similar to the majority of previous studies which report no disease-specific differences in WMH loads in PD patients and agematched normal controls, we did not find a significant difference in WMH burden between controls and PD patients 16,18,38,39 . However, increase in WMH burden was associated with greater cognitive decline and motor and gait deficits, as previously reported in the literature 7,8,[16][17][18][19][20][21] (Figures 3.a, 5.a, and 6.a, respectively).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is particularly important in neurodegenerative disease populations (e.g. Alzheimer's disease and Parkinson's disease), where WMHs are very common findings (van der Flier et al, 2018) and have been shown to interact with neurodegeneration and contribute to cognitive deficits (Dadar et al, 2018c(Dadar et al, , 2019 and therefore their misclassification as GM may systematically bias the findings of such studies.…”
Section: Introductionmentioning
confidence: 99%
“…27 Our previous work with this PD network atrophy measure is supportive of a propagating process. 7,28,29,30 Moreover, the discovery that neurotoxic misfolded α-synuclein can propagate trans-neuronally provides a mechanism for the propagation hypothesis first proposed by Braak et al . 31 This suggests that the pattern of disease could be stereotyped in its spatial distribution as determined by the brains' normal wiring diagram (or connectome) 7 .…”
Section: Discussionmentioning
confidence: 99%